Developmental predictors of offending and persistence in crime: A systematic review of meta-analyses - Basto-Pereira, Miguel (2022)
Meta-analyses have provided major findings about developmental predictors of offending. However, there has been little focus on their relative ability to predict offending behaviour. Therefore, we conducted a systematic review of meta-analyses with two aims: 1) to summarize all well-established knowledge about developmental (explanatory) predictors of offending, and 2) to sort those predictors according to their effect size. The strongest predictors of general offending were related to family/parental dimensions. Delinquent peers, school/employment problems, family problems, certain types of mental health problems, and alcohol/substance abuse were the most important predictors of persistence in crime. Our findings suggest the crucial role of family-related developmental predictors in preventing offending. The predictors of persistence in crime highlight the multisystemic nature of persistent antisocial behaviour.